Celebrating Ethnicity and Nation: American Festive Culture from the Revolution to the Early 20th Century - Heideking, Jürgen (Berghahn Books, 2001)
Celebrating Ethnicity and Nation -- CONTENTS -- EDITORS' PREFACE -- INTRODUCTION -- CELEBRATING THE CONSTITUTION -- THE NATION AS SPECTACLE -- REVOLUTIONARY FESTIVALS ANDPOLITICAL VIOLENCE -- FROM CELEBRATING VICTORY TOCELEBRATING THE NATION -- PERFORMING FREEDOM -- ITALIAN-AMERICANS ANDCOLUMBUS DAY -- "… TO DIVIDE THEIR LOVE" -- CHARITY ON PARADE -- DEMONSTRATING THE VALUESOF 'GEMÜTHLICHKEIT' AND 'CULTUR' -- HALLOWEEN-A "REINVENTED" HOLIDAY -- CLIMATE, IDENTITY, ANDWINTER CARNIVALS IN NORTH AMERICA -- CREATING ANDINSTRUMENTALIZING NATIONALISM -- HISTORICAL BONDING WITH ANEXPIRING HERITAGE
Description based upon print version of record
Keywords: Electronic books